Crises and Development: a Perpetual Vicious Circle for Africa - Grassi,Marzia (2009)
The financial crisis that broke out in 2007 in the northern [1]countries and hit formal financial institutions and investment banks does not bring the same repercussions for African countries. After all, the real economy is organized around informal structures in the majority of these states while formal institutions, the conveyers of crisis, are a recent and still rare reality. However, this does not protect from the growth crisis that followed the financial crisis and which will have a negative impact on African countries as well as all countries around the world. Given the world trade balances and power relationships between countries, some authors propose that this crisis has effectively compromised any possible future for the industrialization that the development of the African continent requires (Ellis, 2009). The paper is structured around a discussion of the history of ideas in the economic sciences and the impact of development policies on the African continent. We begin by reviewing the main lines of thought on development, and then go on to discuss the main ways in which Africa is integrated into the world economy. We conclude that, although the models and the crises thus far experienced have only resulted in rising poverty on the continent and worsened social inequalities between African states and the northern countries, as well as inequalities in effective access to resources, the current crisis may actually be considered potentially positive as it may give rise to a global rethinking of the development model and its impact at the local level. As the crisis originated in the northern states thus making it clear that the negative effects of development may hit all global spaces in the real globalized world, criticism of its underlying and underpinning mechanisms is inevitable. The conclusion suggests that the ideal departure point for rethinking the model of development involves intellectual honesty rather than rapid responses; critical thought should be given again to the social impact of the values underlying economic history and the history of ideas since the advent of capitalism.